DEVELOPING ENGLISH CONVERSATION MATERIAL FOR ISLAMIC HIGH SCHOOL - Ahmad Thoyyib Shofi (E-LINK JOURNAL, 2018)
Students were very difficult to communicate with other people in English effectively. English was learned as a foreign language (EFL) in this country and Indonesian EFL students rarely speak English in their daily lives. English conversation class was taught by no particular book for both teacher and students. This failure was solved by developing an appropriate teaching material for English conversation class at the tenth grade of Islamic Senior High School, which covered conversational guide selection and the used of instructional media. It also aimed at activating the English conversation class. This study used the Research and Development (R&D) design. The data were collected through observation, interview, and questioners and analyzed using a guideline analysis, while the data of the students’ questioners were analyzed using tally system to find the percentage. The subjects of this study were the students of MA Al Karimi Gresik. There were 90 students of the tenth grade students. The material development started with writing material selected from the syllabus and follows CLT principles. The final product was the conversation material for Islamic Senior High Students. It also contained rubric assessment to record the students speaking progress both psychomotor aspect and affective aspect. The product contained Indonesian translation and no answers. Hopefully, the students could be active in responding the questions at the conversation classroom activity. The researcher wanted the English teacher understand the concept of CLT so that he could become the guide, trainer, advisor, and actor who can control the class.